Psychological Peculiarities of Teachers with Different Work Capacity Levels - O. I. Dorogina (Russian State Vocational Pedagogical University, 2015)
The paper considers the issue of teacher's work capacity optimization. The research is aimed at defining teachers' psychological peculiarities relating to their work capacity level and creating the assistance program for its optimization. In the course of the program implementation, its effectiveness has being proved, the low work capacity being optimized by developing self-control, emotional stability and decreasing the aggressive reactions in frustrating situations. The research findings can be applied while creating programs for teachers' further training as well as for students training courses.